Implementasi Peraturan Menteri Perhubungan Nomor PM 63 Tahun 2019 Tentang Standar Pelayanan Minimum Angkutan Orang Dengan Kereta Api Dalam Kemudahan Dan Kenyamanan Layanan Di Stasiun Kereta Api Medan - Ali Putra P Harahap; R Hamdani Harahap; Isnaini Isnaini (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this researcher is to analyze the implementation and obstacles in the Regulation of the Minister of Transportation Number PM 63 of 2019 concerning Minimum Service Standards for Transportation of People by Train in the Ease and Convenience of Service at the Medan Train Station. In this study using a descriptive method using a qualitative approach, how to collect data related to the problem being studied so that it can be explained descriptively. Refers to George Edwards III's theory, namely: communication, resources, disposition and bureaucratic structure. The results of the study show that the implementation of the Minister of Transportation Regulation Number PM 63 of 2019 concerning Minimum Service Standards for Transportation of People by Train in the Ease and Convenience of Service at the Medan Train Station from the communication dimension is still not optimal in terms of the availability of written information which is still minimal, resources are not yet optimal. such as the absence of parking spaces and the available information is not clear, the disposition is still experiencing obstacles such as the attitude of some officers who are still not responsive to prospective passengers, the bureaucratic structure is not maximized in terms of coordination between work units and the placement of officers in the station area is very minimal.